Comparison the Effectiveness of Psychological Empowerment Package Based on Experiences of Divorced Women and Reality Therapy on Sexual Self-Esteem in Women Seeking Divorce - Sedigheh Esmaili; Mohammad Khayyer; Amir Hoshang Mehryar (Iranian Evolutionary Educational Psychology Journal, 2025)
Objective: The current investigation sought to evaluate the efficacy of a psychological empowerment intervention grounded in the lived experiences of divorced women alongside reality therapy in relation to the sexual self-esteem of women pursuing divorce. Methods: This study adopted a quasi-experimental framework characterized by a pre-test and post-test design incorporating a control group. The statistical population encompassed all women seeking divorce who accessed the dispute resolution services in Lar city during the year 2019, from which a sample of 45 individuals was drawn. The instrument employed for data collection was the Sexual Self-Esteem Scale. Both univariate and multivariate analyses of covariance were utilized to assess the research hypotheses. Results: The mean scores pertaining to sexual self-esteem across the three investigational groups exhibited a statistically significant difference. Findings from the Tukey test revealed a notable effectiveness of both training methodologies at the 0.05 significance level. Nevertheless, no statistically significant difference was detected regarding the comparative efficacy of the two approaches. Conclusions: Consequently, imparting the aforementioned skills to couples may prove beneficial and effective in mitigating and preventing numerous conflicts that arise between partners.